The influence of sex and maturation on landing biomechanics: implications for anterior cruciate ligament injury - Sigward, S. M.; Pollard, C. D.; Powers, C. M. (Scandinavian Journal of Medicine & Science in Sports, 2012)
During landing and cutting, females exhibit greater frontal plane moments at the knee (internal knee adductor moments or external knee abduction moments) and favor the use of the knee extensors over the hip extensors to attenuate impact forces when compared with males. However, it is not known when this biomechanical profile emerges. The purpose of this study was to compare landing biomechanics between sexes across maturation levels. One hundred and nineteen male and female soccer players (9-22 years) participated. Subjects were grouped based on maturational development. Lower extremity kinematics and kinetics were obtained during a drop-land task. Dependent variables included the average internal knee adductor moment and sagittal plane knee/hip moment and energy absorption ratios during the deceleration phase of landing. When averaged across maturation levels, females demonstrated greater internal knee adductor moments (0.06±0.03 vs 0.01±0.02 N m/kg m; P<0.005), knee/hip extensor moment ratios (2.0±0.1 vs 1.4±0.1 N m/kg m; P<0.001) and knee/hip energy absorption ratios (2.9±0.1 vs 1.96±0.1 N m/kg m; P<0.001) compared with males. Higher knee adductor moments combined with disproportionate use of knee extensors relative to hip extensors observed in females reflect a biomechanical pattern that increases anterior cruciate ligament loading. This biomechanical strategy already was established in pre-pubertal female athletes.